COMPARISON OF EFFICACY OF YOGURT VERSUS PROBIOTICS FOR THE MANAGEMENT OF ACUTE DIARRHOEA - Anjum , Bilal Ali; Hussain, Maqbool; Iqbal, Muhammad Bilal; Zafar, Sehrish; Haider, Nighat; Nawab, Izza (Journal of Ayub Medical College Abbottabad, 2022)
Background: The advantages of probiotic administration for acute diarrhoea are mainly shorter duration of symptoms as well as reduced number of stools per day while use of traditional yogurt has similar results. So, this study was conducted to compare the efficacy of yogurt with probiotic in children with acute gastroenteritis. Methods: This randomized controlled trial was conducted at department of Pediatrics, Children Hospital, Pakistan Institute of Medical Sciences, Islamabad over 1 year. A total of nine hundred and thirty (930) children between 1-5 years of age presenting with acute diarrhoea were enrolled and equally randomized to Group-A (yogurt) and Group-B (lactobacillus rhamnosus) with ORS. The primary outcome was mean frequency of diarrhoea in first 24 hours after initiation of treatment in both the groups. Results: Gender distribution revealed that out of 930 patients, 643 (69.1%) were male and 287 (30.9%) were female while the mean age was 3.14±1.18 years. Mean duration of disease was 4.23±2.02 days. Mean no. of stools in first 24 hours after treatment in Group-A (yogurt) was 3.25±1.64 and 3.29±1.74 in Group-B (probiotics). Student t-test for independent samples was applied and no significant difference was found between the two groups (p=0.713). Conclusions: Mean frequency of diarrhoea in first 24 hours after treatment with traditional yogurt and commercially available probiotics was not statistically significant in this study.